EFFECTS OF Al2O3 NANOPARTICLES ADDITION ON HARDNESS AND THERMAL PROPERTIES OF Al-Zr-Ce/Al2O3 WITH 3 Wt-% Mg NANOCOMPOSITE PRODUCED BY STIR CASTING - Rd. Panji Maulana; Kirman M.; Agus Sukarto W; Anne Zulfia (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2015)
EFFECTS OF Al2O3 NANOPARTICLES ADDITION ON HARDNESS AND THERMAL PROPERTIES OF Al-Zr-Ce/Al2O3 WITH 3 Wt-% Mg NANOCOMPOSITE PRODUCED BY STIR CASTING. Al-Zr-Ce alloy reinforced with Al2O3 nanoparticles with 3wt% Mg addition is proposed as one of the alternative material to replaceACSR as aluminum conductor. The composition of the nanocomposite consists of 0.12% Zr, 0.15% Ce, 3% Mg and 0.5-1.5 vf-% Al2O3. Fabrication of the nanocomposite is using stir casting method. Master alloy which consists of aluminum alloyed with Zr and Ce was manufactured. The master alloy was then melted and 3% Mg along with the reinforcement was blended inside the molten metal by stirring with rotational speed of 500 rpm at 850°C in an inert Ar gas environment. Chemical composition test confirmed the composition of alloying elements were close to the design except Ce, that could be related to limitation of OES and fading effect. The density of nanocomposite was decreased, while the porosity was increased with the addition of Al2O3. Nanocomposites’ hardness testing shows hardness increases with further addition of Al2O3, except the composite with 1.5 vf% of reinforcement that had lower hardness. Further addition of Al2O3 reinforcement to nanocomposite reduced its thermal expansion coefficient. SEM observation indicated that the Al2O3 nano particles were agglomerated and did not react to form interface layer. Nanocomposite 1.2 vf-% SEM observation shows that Ce inside of themicro structure did not segregate with Fe and Si, but seemed to react with Mg and Zr.